Respostas

2013-02-27T20:03:42-03:00

Então, a montagem da equação fica:

2/3(x - 1) = 4

2x -2/3 = 4

2x - 2 = 12

2x = 12 + 2

2x = 14

x = 14/2

x = 7

 

 

 

 

2-X => um número
x+1 => seu consecutivo

x + x+1 = 527

2x = 526

x = 263 
portanto os número são 263 e 264

 

 

 

 

 

3-

2013-02-27T20:23:37-03:00

1)

 

2/3  (x-1) = 4

 

2/3x - 2/3 = 4

 

2/3x  = 4 + 2/3

 

2x = 12 + 2   

--------------

        3

 

2x = 14

 

x = 14/2

 

x = 7

 

 

 

2)

 

x + x + 1 = 527

 

2x = 527 - 1

 

2x = 526

 

x = 526/2

 

x = 263            entao os numeros sao 263 e 264

 

 

 

 

3)

 

2 (x-1) - 3 = 25

 

2x - 2 - 3 = 25

 

2x = 25 + 2 + 3

 

2x = 30

 

x = 30/2

 

x = 15

1 5 1